Potential and Opportunities for Development of Tourism in Ukraine - KOVALCHUK, Yurii; FURMAN, Irina; HUMENYUK, Halyna; KUCHER, Anatolii (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020DO - 10.14505//jemt.v11.1(41).22, 2020)
The purpose of the research is to evaluate the potential and opportunities for the development of tourist activity in the regions of Ukraine in the present context using a method of analysis of the functioning environment. Twelve regions of Ukraine were found to have high tourism development potential, but the other thirteen did not have enough revenue from tourism services to cover labor and operating costs. In Ukraine, Dnipropetrovs’k (60.5%), Ternopil’ (41.4%), Ivano-Frankivs’k (39.1%) and Chernihiv (33.3%) regions have the greatest potential for improving the provision of tourist services. The potential of other regions ranges from 23.0% to 28.2%. The level of realization of existing opportunities and the level of losses from tourist activity in the regions of Ukraine were calculated, and it is allowed to identify the high level of realization of development opportunities in the Dnipropetrovs’k region, but four regions (Kharkiv, Rivne, Poltava, Mykolaiv ones) suffered losses. The results of the study can be used in strategic and operational planning of tourism development in the regions of Ukraine and in improving the efficiency of the tourism business.